Diversity of Plastid Types and Their Interconversions - Choi, Heebak; Yi, Taegyu; Ha, Sun-Hwa (Frontiers in Plant Science, 2021)
Plastids are pivotal subcellular organelles that have evolved to perform specialized functions in plant cells, including photosynthesis and the production and storage of metabolites. They come in a variety of forms with different characteristics, enabling them to function in a diverse array of organ/tissue/cell-specific developmental processes and with a variety of environmental signals. Here, we have comprehensively reviewed the distinctive roles of plastids and their transition statuses, according to their features. Furthermore, the most recent understanding of their regulatory mechanisms is highlighted at both transcriptional and post-translational levels, with a focus on the greening and non-greening phenotypes.